Patterns of Nucleotide Deletion and Insertion Inferred from Bacterial Pseudogenes. (2nd July 2018) - Danneels, Bram; Pinto-Carbó, Marta; Carlier, Aurelien
Abstract: Pseudogenes are a paradigm of neutral evolution and their study has the potential to reveal intrinsic mutational biases. However, this potential is mitigated by the fact that pseudogenes are quickly purged from bacterial genomes. Here, we assembled a large set of pseudogenes from genomes experiencing reductive evolution as well as functional references for which we could establish reliable phylogenetic relationships. Using this unique dataset, we identified 857 independent insertion and deletion mutations and discover a pervasive bias towards deletions, but not insertions, with sizes multiples of 3 nt. We further show that selective constraints for the preservation of gene frame are unlikely to account for the observed mutational bias and propose that a mechanistic bias in alternative end-joining repair, a recombination-independent double strand break DNA repair mechanism, is responsible for the accumulation of 3 n deletions.